Therapeutic effect of Curcuma longa L. on the nonalcoholic fatty liver disease (NAFLD) physiopathology due fructose consumption - Hasimoto, Fabiana Kurokawa [UNESP]; Francisqueti-Ferron, Fabiane Valentini [UNESP]; Costa, Mariane Róvero [UNESP]; de Souza, Marajane Bruno [UNESP]; Aun, Aline Garcia [UNESP]; Nogueira, Flávia Ribeiro [UNESP]; Alves, Pedro Henrique Rizzi [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Garcia, Jéssica Leite [UNESP]; de Almeida Silva, Carol Cristina Vágula [UNESP]; Ferron, Artur Junio Togneri [UNESP]; Minatel, Igor Otávio [UNESP]; et al. (My University, 2020)
Purpose: The consumption of products containing fructose is associated with metabolic disorders and nonalcoholic fatty liver disease (NAFLD). Several pathways have been described associating the fructose intake and liver damage, among them the reduced peroxisome proliferator-activated receptor alpha (PPAR-α) expression, insulin resistance, inflammation, and oxidative stress. Curcuma longa L. is a member of the Zingiberaceae family and has traditionally been used as a medicinal herb. The aim was to verify the therapeutic effect of Curcuma longa L. in the physiopathology of NAFLD due to the fructose consumption. Methods: During 16 weeks, animals (n = 12) received standard chow + fructose in drinking water (30%) ad libitum. After, animals were randomly allocated to receive placebo treatment (fructose, n = 6) or Curcuma longa L. treatment (fructose + Cl, n = 6) for further 8 weeks. Both groups continued receiving standard chow + fructose in drinking water (30%) ad libitum. Results: Curcuma longa L. was effective to reduce insulin resistance and triglycerides levels, increase PPAR-α protein expression in liver, and attenuate macrovesicular steatosis, liver IL-6 levels, and oxidative stress (with lower protein carbonylation, MDA, and DNA damage and increase in SOD and catalase antioxidant enzymes) induced by fructose consumption. Conclusion: Curcuma longa L. treatment was effective to modulate the physiopathology of NAFLD due to fructose consumption.
Keywords: Antioxidant; Curcumin; Liver; Polyphenols